Assessment of carbonic anhydrase IX expression and extracellular pH in B-cell lymphoma cell line models. Issue 5 (May 2015) - Chen, Liu Qi; Howison, Christine M.; Spier, Catherine; Stopeck, Alison T.; Malm, Scott W.; Pagel, Mark D.; Baker, Amanda F.
Abstract The expression of carbonic anhydrase IX (CA IX) and its relationship to acidosis in lymphomas has not been widely studied. We investigated the protein expression of CA IX in a human B-cell lymphoma tissue microarray, and in Raji, Ramos and Granta 519 lymphoma cell lines and tumor models, while also investigating the relationship with hypoxia. An imaging method, acidoCEST magnetic resonance imaging (MRI), was used to estimate lymphoma xenograft extracellular pH (pHe). Our results showed that clinical lymphoma tissues and cell line models in vitro and in vivo had moderate CA IX expression. Although in vitro studies showed that CA IX expression was induced by hypoxia, in vivo studies did not show this correlation. Untreated lymphoma xenograft tumor pHe had acidic fractions, and an acidity score was qualitatively correlated with CA IX expression. Therefore, CA IX is expressed in B-cell lymphomas and is qualitatively correlated with extracellular acidosis in xenograft tumor models.